Rhoptry protein 5 (ROP5) Is a Key Virulence Factor in Neospora caninum - Ma, Lei; Liu, Jing; Li, Muzi; Fu, Yong; Zhang, Xiao; Liu, Qun (Frontiers in Microbiology, 2017)
Neospora caninum, of the Apicomplexa phylum, is a common cause of abortions in cattle and nervous system dysfunction in dogs. Rhoptry proteins of Apicomplexa play an important role in virulence. The objectives of this study were to study functions of NcROP5 in N. caninum by deleting the NcROP5 gene from the wild Nc-1 strain. We selected NcROP5 in ToxoDB and successfully constructed an NcROP5 gene-deleted vector, pTCR-NcROP5-CD KO. Then we screened the NcROP5 knockout strains (ΔNcROP5) at the gene, protein and transcription levels. Plaque assay, host cell invasion assay and intracellular proliferation test showed that the ΔNcROP5 strain had less plaque space, weakened invasion capacity and slower intracellular growth. Animal testing showed significantly lower cerebral load of ΔNcROP5 than the load of the Nc-1 strain, as well as a loss of virulence for the ΔNcROP5 strains. Phenotypic analyses using the label-free LC-MS/MS assay-based proteomic method and KEGG pathway enrichment analysis showed a reduction of NcGRA7 transcription and altered expression of multiple proteins including the apicomplexan family of binding proteins. The present study indicated that ROP5 is a key virulence factor in N. caninum in mice. The proteomic profiling of Nc-1 and ΔNcROP5 provided some data on differential proteins. These data provide a foundation for future research of protein functions in N. caninum.